Improving Information Services in Smart-City Areas by Means of Modern Technologies - Rykowski, Jarogniew; Gromadziński, Jakub (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
The aim of the article is, firstly, to show the evolution of information services in public space in connection with the emergence of new technologies. Secondly, the article proposes new ideas for providing selected information services using the latest technological and organisational solutions. The article aims to show that new technologies not only significantly improve the flow of information but also become the basis for new services in smart spaces. As a leading example, virtual announcement columns, the task of which is to facilitate access to local information depending on a given place (location) and time, are described. These boards are the equivalent of traditional places for posting local announcements and messages in paper form. However, the comfort of their use is greater, and thanks to this, their usefulness in public space is also more significant. As a result, the collection of residents’ opinions, ad-hoc help for tourists, etc., have been improved. The proposed solutions are based on new technologies, such as Bluetooth location beacons with variable information and QR codes. They are addressed to owners of mobile phones and can be used in public urban areas.